Forest floor vegetation response to nitrogen deposition in Europe. (20th November 2013) - Dirnböck, Thomas; Grandin, Ulf; Bernhardt‐Römermann, Markus; Beudert, Burkhardt; Canullo, Roberto; Forsius, Martin; Grabner, Maria‐Theresia; Holmberg, Maria; Kleemola, Sirpa; Lundin, Lars; Mirtl, Michael; Neumann, Markus; et al.
Abstract Chronic nitrogen (N) deposition is a threat to biodiversity that results from the eutrophication of ecosystems. We studied long‐term monitoring data from 28 forest sites with a total of 1, 335 permanent forest floor vegetation plots from northern Fennoscandia to southern Italy to analyse temporal trends in vascular plant species cover and diversity. We found that the cover of plant species which prefer nutrient‐poor soils (oligotrophic species) decreased the more the measured N deposition exceeded the empirical critical load (CL) for eutrophication effects (P = 0.002). Although species preferring nutrient‐rich sites (eutrophic species) did not experience a significantly increase in cover (P = 0.440), in comparison to oligotrophic species they had a marginally higher proportion among new occurring species (P = 0.091). The observed gradual replacement of oligotrophic species by eutrophic species as a response to N deposition seems to be a general pattern, as it was consistent on the European scale. Contrary to species cover changes, neither the decrease in species richness nor of homogeneity correlated with nitrogen CL exceedance (ExCLempN). We assume that the lack of diversity changes resulted from the restricted time period of our observations. Although existing habitat‐specific empirical CL still hold some uncertainty, we exemplify that they are useful indicators for the sensitivity of forest floor vegetation to N deposition.